Correlation of OPG/RANKL in patients with thalassemia major at the center of Haemoglobinopathy Lushnje, Albania - Jorida Zoga; Majlinda Kallco; Etleva Refatllari (European Scientific Journal, ESJ, 2024)
Osteoporosis is an important cause of morbidity in hemoglobinopathy patients. It is characterized by low bone mass and disruption of bone architecture, resulting in reduced bone strength and increased risk of fractures. Osteoprotegerin (OPG) and receptor activator of NF-kappa-B ligand (RANKL) have recently been implicated in the pathogenesis of various types of osteoporosis. Our study aimed to determine the correlation between OPG/RANKL and patients affected by thalassemia major at the Center of Hemoglobinopathy in Lushnje. Methods: We measured serum OPG and RANKL levels in 70 patients with Thalassemia major and 67 healthy controls, determining correlations with BMD. Results: Serum OPG levels were significantly lower in thalassemic patients compared to the control group. Serum RANKL levels were higher in β-thalassemia patients compared to controls. 31.1% of our patients with Thalassemia major had osteoporosis and 21.6 % had osteopenia. We found a correlation between OPG-BMD (r=-0.768, p=0.000, and RANKL-BMD (r=0.468; p=0.000). Conclusion: OPG and RANKL in Thalassemia major patients should be considered as the main factors responsible for osteoclast activation.